Urinary bladder paraganglioma in pregnancy: a case report and literature review - Yadong Sun; Yadong Sun; Lili Chen; Yongxiang Li; Yongxiang Li; Liang Qiao; Liang Qiao (Frontiers in Medicine)
Urinary bladder paragangliomas (UBPs) are rare tumors of chromaffin tissue originating from the sympathetic innervation of the bladder wall. It constitutes less than 0.05% of bladder tumors and 0.7% of all paragangliomas. The occurrence of UBP during pregnancy is extremely rare. Hypertensive disorders of pregnancy due to paraganglioma significantly increase the risk of adverse maternal and fetal outcomes. Herein, we report the case of UBP in a 28-year-old woman at 34 weeks’ gestation. The baby was successfully delivered, and bladder tumor was excised via partial cystectomy during the same surgical procedure. In addition, we conducted a literature review of paragangliomas during pregnancy, as there are only a few case reports of such diseases and there is no consensus on standard treatment. This study aims to contribute to the enhancement of the diagnosis and treatment of UBP during pregnancy.